How to record learning activity with a smartphone on lesson study program. Issue 4 (February 2019) - Kuntadi, I; Widiaty, I; Ana, A; Widaningsih, L; Mubaroq, S R
Abstract: This study was motivated by the desire to digitally record and document students' learning activities in a program namely lesson study since so far, the observation on lesson study has been conducted manually. Thus, the purpose of the study was to identify on how to record students' behaviors during lesson study using a smartphone. There are two techniques of learning activity recording. First, to record learning activities classically, the technique used is placing a smartphone camera horizontally from the back of the classroom. Second, to have more detailed recording for each individual, there needs to be a tripod to help zoom in and zoom out during the lesson. The results of the study show that the digital observation using a smartphone enabled the teachers have more detailed and focused documentation. In addition, there are to other benefits that the recording could be replayed to see the lesson reflection in accordance with the lesson plan and it could also be discussed further in the context of collaborative lesson study.